Modeling of Continuous environmentAL education: a foreign experience analysis - Lyudmila G. Murtazina; Ilgizar T. Gaisin (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The increase in public attention caused by ecological problems had a profound effect on environmental education. The policy document "Agenda XXI" adopted in 1992 expanded environmental education content towards education for sustainable development. Many countries, including the United States, began a comprehensive planning process of education for sustainable development. In the implementation of strategies of environmental education for sustainable development many developed countries used a coordinated comprehensive approach that comprises the participation of civil society, local communities, the scientific community. Despite the fact that in the US there is no single federal standard in the field of environmental education, each state has defined and uses eco-educational standards in relation to a particular region. On the example of environmentally oriented Ohio, the authors of the article consider conceptual approaches to the modeling of continuous environmental education in the United States. The article analyzes the foreign approaches to content, program design, implementation and evaluation of quality. According to the authors a special role in the development of continuous environmental education in the United States belongs to the "green" (sustainable) schools, whose creation gave a new impulse to the implementation of sustainable initiatives for the planning, distribution, implementation, monitoring sustainability and environmental education programs in schools, universities and local community.